2012
DOI: 10.1155/2012/341260
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Detection of Poly(amidoamine) PAMAM Dendrimers Using Immunoimaging Scanning Probe Microscopy

Abstract: Immunoimaging scanning probe microscopy was utilized for the low-level detection and quantification of biotinylated G4 poly(amidoamine) PAMAM dendrimers. Results were compared to those of high-performance liquid chromatography (HPLC) and found to provide a vastly improved analytical method for the low-level detection of dendrimers, improving the limit of detection by a factor of 1000 (LOD = 2.5 × 10−13 moles). The biorecognition method is reproducible and shows high specificity and good accuracy. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…As a result, the presence of dense concentration and globular shape of dendrimer might have provided better interaction between antigen and sensing layer 79 . Therefore, 10 mM PAMAM dendrimer was established as optimal concentration, which is in agreement with those reported in the literature 80 .…”
Section: Resultssupporting
confidence: 89%
“…As a result, the presence of dense concentration and globular shape of dendrimer might have provided better interaction between antigen and sensing layer 79 . Therefore, 10 mM PAMAM dendrimer was established as optimal concentration, which is in agreement with those reported in the literature 80 .…”
Section: Resultssupporting
confidence: 89%
“…Cross-sectional line scans along the dotted segments in Figure 4b,c are illustrated in Figure 4d. The particle heights obtained from four distinct particles represented in Figure 4d range from 2.7–10 nm which agrees with dendrimer size obtained by AFM analysis reported by Li et al and with dendrimer analysis observed in our previous work [38,68]. Feature width, from Figure 4d, is 30–50 nm which is 7–13 times larger than the expected diameter of G4 PAMAM dendrimers, 4 nm [69].…”
Section: Resultssupporting
confidence: 89%
“…Most existing instrumental methods, e.g., IR spectroscopy, NMR spectroscopy, size-exclusion chromatography, and mass spectrometry (MS) especially with matrix-assisted laser desorption/ionization, have been applied in investigations of the synthesis of dendrimers to optimize aspects such as control of structural defects and functionalization of the surface [2,3,[8][9][10][11][12][13][14]. Sophisticated microscopy (image-based) techniques or chromatographic systems are being used as the tool of choice for detection, quantification, and localization of nanoparticles in cells to describe their metabolic pathways [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Sophisticated microscopy (image-based) techniques or chromatographic systems are being used as the tool of choice for detection, quantification, and localization of nanoparticles in cells to describe their metabolic pathways [8][9][10]. Soft ionization technique such as electrospray ionization (ESI) MS have been shown to efficiently promote ionization of dendrimers ranging from low to high generations.…”
Section: Introductionmentioning
confidence: 99%